SMALLMOUTH BASS FLIES TOP TO BOTTOM - Villwock, Jake, 1986-; Wissmath, Dusty (Guilford, United States : STACKPOLE BOOKS, 2021)
Smallmouth bass swim in lakes and rivers across the United States and Canada and are a premier fly-rod game fish in almost every way-they take flies readily, feed on diverse foods for a long period of time, tolerate higher water temperatures than trout, and fight harder than any other North American freshwater fish their size. This is the first book dedicated to the best modern flies for these fish that includes both detailed step-by-step tying instructions as well as top patterns and recipes for flies that cover the complete water column, from top to bottom. With over 500 full-color step-by-step images and 300 patterns by today's top tiers from around the country, this book is the definitive resource for smallmouth bass.
Includes index
Keywords: Smallmouth bass fishing -- Guidebooks; Fly fishing